2007
DOI: 10.1002/hep.21925
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-β/δ protects against chemically induced liver toxicity in mice

Abstract: Potential functional roles for the peroxisome proliferator-activated receptor-␤/␦ (PPAR␤/␦) in skeletal muscle fatty acid catabolism and epithelial carcinogenesis have recently been described. Whereas PPAR␤/␦ is expressed in liver, its function in this tissue is less clear. To determine the role of PPAR␤/␦ in chemically induced liver toxicity, wild-type and PPAR␤/␦-null mice were treated with azoxymethane (AOM) and markers of liver toxicity examined. Bile duct hyperplasia, regenerative hyperplasia, and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
67
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 67 publications
12
67
0
Order By: Relevance
“…Expression of Cyp2b10 is thought to be mediated by CAR activation (18). However, the present study clearly showed that ethanol treatment did not influence the relative expression of CAR as also observed in a previous study (10) or enhance the nuclear translocation of CAR following treatment with ethanol. Because the translocation of CAR to the nucleus is required to initiate target gene expression (19 -21), this illustrates a unique finding from the present study because the results indicate that PPAR␤/␦, rather than CAR, is required for up-regulation of Cyp2b10 in response to ethanol.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Expression of Cyp2b10 is thought to be mediated by CAR activation (18). However, the present study clearly showed that ethanol treatment did not influence the relative expression of CAR as also observed in a previous study (10) or enhance the nuclear translocation of CAR following treatment with ethanol. Because the translocation of CAR to the nucleus is required to initiate target gene expression (19 -21), this illustrates a unique finding from the present study because the results indicate that PPAR␤/␦, rather than CAR, is required for up-regulation of Cyp2b10 in response to ethanol.…”
Section: Discussionsupporting
confidence: 87%
“…1A). This was of interest because previous studies demonstrated a similar PPAR␤/␦-dependent effect on the hepatic expression of CYP2B10 in mice exposed to carbon tetrachloride (10). Overall, ethanol exposure significantly altered expression of 358 genes or 146 genes, in livers of Ppar␤/␦ ϩ/ϩ or Ppar␤/␦ Ϫ/Ϫ mice, respectively (Fig.…”
Section: Ppar␤/␦ Modulates Ethanol-induced Hepatic Cyp2b10mentioning
confidence: 53%
See 2 more Smart Citations
“…However, little is known about the possibility that isoflavones activate PPARβ/ δ, which plays a critical role in the regulation of metabolic homeostasis, and also in cardiac lipid metabolism (15,16), fetal development (17), inhibition of human cancer cell line growth (18), protection against liver toxicity (19), modulation of inflammation (6,20), and improved skeletal muscle oxidative enzyme activity in obese patients with type 2 diabetes mellitus (21).…”
Section: Discussionmentioning
confidence: 99%